Physically unclonable functions based on a controlled ring oscillator - Alexander A. Ivaniuk; Vyacheslav N. Yarmolik (Безопасность информационных технологий, 2023)
The problem of constructing a new class of physically unclonable functions (PUF) based on a controlled ring oscillator (CRO) has beeb solved. The relevance of the creation of CROPUF is associated with the active development of physical cryptography used for the purposes of identifying electronic products and generating cryptographic keys. It is shown that classical physically unclonable functions based on ring oscillators (ROPUF) are characterized by large hardware redundancy due to the need to implement a large number of ROs, since each bit of the response requires an independent pair of real ROs. At the same time ROPUFs are characterized by better statistical properties compared to PUFs of the arbiter type and do not require ideal symmetry and identity of implemented ROs. As an alternative to ROPUF, a new class of physically unclonable functions is proposed, namely, CROPUF, which uses controlled ring oscillators based on controlling the frequency of generated pulses without changing the functionality and structure of the oscillator. An important advantage of the CRO is a possibility of implementing on its basis a set of ROs, the number of which reaches 2m, where m is the number of stages of the oscillator, and each of them is determined by the submitted request. The three alternative structures for the proposed PUF, namely CROPUF1, CROPUF2 and CROPUF3   are considered. Their main advantages and disadvantages are shown, including in the case of two implementation options, namely on programmed logic (FPGA) and arbitrary logic (ASIC). As a basic option for implementation on FPGA, CROPUF2 is considered less prone to inter-chip and, more importantly, intra-chip dependence caused by the technological features of the production process. Practical studies were carried out by implementing CROPUF2 on modern FPGAs, evaluating its performance and its main characteristics. The operability of a new class of PUFs when implemented on programmable logic, as well as high rates of their main statistical characteristics, has been experimentally confirmed.